2021
DOI: 10.3390/ijerph19010427
|View full text |Cite
|
Sign up to set email alerts
|

Child Domestic Work, Violence, and Health Outcomes: A Rapid Systematic Review

Abstract: This rapid systematic review describes violence and health outcomes among child domestic workers (CDWs) taken from 17 studies conducted in low- and middle-income countries. Our analysis estimated the median reported rates of violence in CDWs aged 5–17-year-olds to be 56.2% (emotional; range: 13–92%), 18.9% (physical; range: 1.7–71.4%), and 2.2% (sexual; range: 0–62%). Both boys and girls reported emotional abuse and sexual violence with emotional abuse being the most common. In Ethiopia and India, violence was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
2
6
0
Order By: Relevance
“…Like previous studies, our findings show that apart from domestic work, CDWs are also engaged in more hazardous activities and economic labour activities [ 15 , 34 ]. CDWs may also be doing economic activities, especially within the context of household duties.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Like previous studies, our findings show that apart from domestic work, CDWs are also engaged in more hazardous activities and economic labour activities [ 15 , 34 ]. CDWs may also be doing economic activities, especially within the context of household duties.…”
Section: Discussionsupporting
confidence: 85%
“…Being a CDW is associated with various hazards linked to denial of rights which can have irreversible physical and psychological impacts on health and wellbeing, such as access to education and health care, and the right to rest, leisure, play, and recreation. A recent systematic review found a large variation in experiences of violence among CDWs in Low and Middle Income Countries (LMICs), with over half of CDWs experiencing emotional violence (56%), and 19% and 2% experiencing physical and sexual violence, respectively (median rates) [ 15 ]. Across studies, between 7% and 68% of CDWs reported work-related illness and injuries, and one third to half had received no medical treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Child labour gravely impacts physical health (Batomen Kuimi, Oppong-Nkrumah, Kaufman, Nazif-Munoz, & Nandi, 2018;Pérez-Herrera et al, 2019;Scott & Pocock, 2021), mental health (Meyer, Yu, Rieders, & Stark, 2020;Ornek, 2017;Ornek & Esin, 2018;Scott & Pocock, 2021;Sturrock & Hodes, 2016), childhood maltreatment such as abuse and neglect (Dhakal et al, 2019;Jonsson et al, 2021;Pandey et al, 2020;Thi, Zimmerman, Pocock, Chan, & Ranganathan, 2022), and nutritional status (Batomen Kuimi et al, 2018). According to recent studies, levels of depression and anxiety among children are already high, and they are increasing (Meyer et al, 2020;Sturrock & Hodes, 2016;Wickham, Whitehead, Taylor-Robinson, & Barr, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, child labourers are under higher risk of health problems due to unequal life and working conditions (Ornek & Sevim, 2018) work may also have difficulties in acquiring and maintaining healthy lifestyle behaviours such as healthy eating and exercise (Batomen Kuimi et al, 2018). In addition, they are more likely to be exposed to labour violations, fatal and non-fatal work accidents, and injury at the workplace compared to adults or peer groups attending school full-time (Batomen Kuimi et al, 2018;Habib et al, 2021;Thi et al, 2022). For example, nearly 2,500 workers lost their lives in 2020 due to work accidents in Turkey, among whom 3% were younger than 17 years of age (22 workers were younger than 14, and 46 were 15-17 years in age).…”
Section: Introductionmentioning
confidence: 99%